The genus Syspira Simon, 1895 (Araneae: Miturgidae) from Hispaniola, with the description of four new species - Sánchez-Ruiz, Alexander; de Los Santos, Gabriel; Brescovit, Antonio D.; Bonaldo, Alexandre B. (Zootaxa, 2020)
The species of Syspira Simon from Hispaniola are revised and detailed documentation is provided for all known species from this island. Four new species (Syspira alayoni sp. n., S.  armasi sp. n., S.  barbacoa sp. n., and S.  bryantae sp. n.), and the unknown male of Syspira agujas Brescovit, Sánchez-Ruiz & Bonaldo are described. New distribution records were found for three known species (S. agujas, S. cimitarra Brescovit, Sánchez-Ruiz & Bonaldo and S.  medialuna Brescovit, Sánchez-Ruiz & Bonaldo). The Hispaniolan endemic species Teminius monticola (Bryant, 1948) is transferred to Syspira based on the revision of its holotype. A key for Hispaniola Syspira species is provided. These species can be separated into two distinct groups based on features of the male palpal morphology and female genitalia: the cimitarra group including S. cimitarra, S. jimmyi Brescovit, Sánchez-Ruiz & Bonaldo, S. alayoni and S. barbacoa sp. n., and the agujas group including S. agujas, S. medialuna, S. monticola comb. n., S. armasi sp. n. and S. bryantae sp. n.